CMV induces expansion of highly polyfunctional CD4+ T cell subset coexpressing CD57 and CD154 - Alejandra Pera; Anusha Vasudev; Crystal Tan; Hassen Kared; Rafael Solana; Anis Larbi (2016)
Abstract CD4+ T cells are essential for human CMV infection control. CMV-specific CD4+ T cells possess antiviral functions and participate in anti-CMV humoral/cellular responses. In the elderly, CMV infection impairs immunity to other viruses and has been traditionally associated with T cell senescence; however, recent results suggest that, in younger people, CMV confers immune protection against other pathogens (heterologous immunity). To shed light on this controversy, we analyzed latent CMV infection effects on the quality of young individuals’ immune response, specifically, the presence of polyfunctional T cells through an extensive phenotypic and functional characterization of the CD4+ T cell subset. CD154 expression, degranulation (CD107a), and cytokine production (IFN-γ, TNF-α, and IL-2) as well as T cell phenotype markers (CD57, CD28, and CD27) were analyzed. We demonstrate that CD4+ T cells that coexpress CD57 and CD154, which are exclusively present in CMV-positive individuals, are the most polyfunctional CD4+ subset, whereas CD4+CD27+CD28− T cells associate with lower polyfunctionality. Conversely, the frequency of CD4+CD28+ T cells correlates with higher polyfunctionality of CD4+CD57− T cells from CMV-seronegative individuals and CD4+CD57+CD154+ T cells from CMV-seropositive individuals. Thus, polyfunctionality is a property of central memory CD4+ T cells in CMV-seronegative individuals, whereas after CMV infection, polyfunctional T cells become highly differentiated, which allows efficient eradication of infections. We extend previous observations of the impact of CMV on CD8+ T cell functionality to the CD4+ T cell compartment, revealing CD57 as a polyfunctionality marker of T cells which expands after CMV infection. CD57+ T cells have been associated with inflammatory conditions, but their potential role in the response against infectious disease and vaccination should now be investigated.